MOTIVASI DAN PERSEPSI WISATAWAN DOMESTIK BERWISATA DIVING DI KEPULAUAN DERAWAN, KALIMANTAN TIMUR - Humaira, Nasya Locita Alya; Suwena, I Ketut; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023)DO - 10.24843/IPTA.2023.v11.i01.p12, 2023)
The research was conducted to see the motivation and perceptions of domestic tourists on a diving tour in the Derawan Islands, Berau Regency, East Kalimantan. The operational definition of research variables consisted of tourists, motivation, perception as the dependent variable with the total using 28 indicators. In determining the sample, the researcher used a purposive sampling method in which the researcher gave an offline questionnaire and online questionnaire via google form to 100 people who were on a diving tour in the Derawan Islands. The data analysis technique used is qualitative. The results showed that the majority of domestic tourists on diving trips were male on average aged 15-24 years. The main motivation of tourists is to go diving in the Derawan Islands because of the beautiful scenery. Tourists as a whole have a very good perception of diving tourism in the Derawan Islands. Based on this, for the development of the Derawan Islands in a further direction, the researcher provides advice for tourism managers to provide education to diving guides.